2022
DOI: 10.1111/bju.15881
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of lymph node staging with prostate‐specific membrane antigen (PSMA) positron emission tomography/computed tomography (PET/CT) and extended pelvic lymph node dissection in node‐positive patients with prostate cancer

Abstract: Objectives To investigate whether patients with suspected pelvic lymph node metastases (molecular imaging [mi] N1) on staging prostate‐specific membrane antigen (PSMA) positron emission tomography/computed tomography (PET/CT) had a different oncological outcome compared to those in whom the PSMA PET/CT did not reveal any pelvic lymph node metastases (miN0). Patients and Methods All patients with pelvic lymph node metastatic (pN1) disease after robot‐assisted radical prostatectomy (RARP) and extended pelvic lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…A recent paper showed that the patients in whom pelvic lymph node metastases were suspected on preoperative PSMA imaging had a significantly increased risk of biochemical disease progression after surgery (Meijer et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper showed that the patients in whom pelvic lymph node metastases were suspected on preoperative PSMA imaging had a significantly increased risk of biochemical disease progression after surgery (Meijer et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…While overall cancer control rates are mostly acceptable for clinically localized PCa after RP, and improved outcome of RP using novel imaging tools such as prostate specific membrane antigen (PSMA) positron emission tomography (PET)/CT and indocyanine green (ICG) guidance might be expected, 20-30% of patients experience a recurrence that initially presents as elevated serum PSA without clinical or radiographic metastases [2,[27][28][29]. However, not all patients with BCR develop disease progression and metastases, and the clinical course of the patients is highly variable.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as previously discussed, the count of positive nodes remains a pivotal prognostic indicator [4], potentially steering us toward contemplating adjuvant interventions for these patients. It is evident that having more than two positive nodes will substantially impact the risk of biochemical recurrence.…”
mentioning
confidence: 90%
“…Unlike the ICG technique, which essentially provides a lymphography of the pelvic template, SPECT‐CT delivers functional imaging that conveys an authentic depiction of the sentinel node. Moreover, as previously discussed, the count of positive nodes remains a pivotal prognostic indicator [4], potentially steering us toward contemplating adjuvant interventions for these patients. It is evident that having more than two positive nodes will substantially impact the risk of biochemical recurrence.…”
mentioning
confidence: 99%